Starter kit for the production of pure and high quality microalgae. - Md Yusoff, Fatimah; Mohamed Din, Mohamed Shariff (2011)

(untitled)
A Novel use of nutrient rich pore water or interstitial water (IW) extracted from aquaculture pond botton sediments is an alternative medium for culturing different pure microalgal species. The medium is prepared by extracting, filtering, sterilizing the interstitial water collected from enriched sludge sediment and finally concentrate the interstitial water nutrient rich liquid extract or powder forms to be used as culture medium by diluting or dissolving it, respectively in water. A microalgae growth initializing kit is produced by packing microalgae isolates with the nutrient rich liquid extract and/or powder